CONSTRUCTION OF QUALITY OPTIMAL REGULATORS AND KALMAN FILTERS - Антонов, В. К. (Proceedings of National Aviation University (archive), 2021)
A modification of the Kalman optimal filtration method is proposed, which provides the ability to control the filtration process, maximum speed and limitation of oscillations. The principle of the cyclic operator of achievement of the purpose consisting in repeated consecutive application of the operator of achievement of the purpose at use of results of its previous applications, on an example of problems of approximation of functions, management, filtering is formulated.